The Influence of Raffi Ahmad's Celebrity Endorsement on Purchase Intention Through Social Media with Brand Image as Mediator and Negative Publicity as Moderation - Muhammad Isnaini Fauzan Zuhri; Erlita Ridanasti (PT SOLUSI EDUKASI BERDIKARI, 2024)
The aim of this research is to examine the influence of celebrity endorsement with the dimensions of likeability, similarity, attractiveness, expertise and trustworthiness so that it can increase purchase intention through social media with brand image as mediation, and negative publicity as moderation. The research method uses a quantitative approach by distributing questionnaires to 180 social media user respondents in Indonesia who know celebrity endorser Raffi Ahmad. Data analysis was carried out using PLS-SEM with SmartPLS 4.1.0.4 software. The results of the study stated that celebrity endorsement with the dimensions of likeability, similarity, attractiveness, expertise and trustworthiness had a positive and significant effect on brand image and purchase intention. On the other hand, the mediating brand image does not have a positive and significant effect on purchase intention. The research results also state that negative publicity as a moderator of celebrity endorsement has a positive and significant effect on purchase intentions.